Variability and repeatability of quantitative, SD-OCT doppler blood flow in young and elderly healthy subjects - Tayyari, Faryan; Yusof @ Alias, Firdaus; Vymyslicky, Michal; Flanagan, John G; Hudson, Christopher (The Association for Research in Vision and Ophthalmology, Inc., 2014)
Purpose: The purpose was to determine the within-session variability and between-session repeatability of SD-OCT Doppler measurement of retinal blood flow in young and elderly healthy subjects. Methods: SD-OCT Doppler blood flow was non-invasively measured using the RTVue system (Optovue Inc., USA). One eye of each of 6 healthy young (mean age 25.7; SD 3.5 years) and 6 healthy elderly (mean age 63.1; SD 1.8 years) subjects was randomly selected for the study and the pupil was dilated using Mydriacyl 1%. A double circular scanning pattern was employed. A minimum of six separate SD-OCT Doppler measurements (i.e. each separate measurement comprising an upper nasal pupil scan and a lower nasal pupil scan) were acquired at each session. Measurements were repeated on a second day. Retinal blood flow was calculated, using data from valid scans only, by summing flow from all detectable venules. The coefficient of variation and the coefficient of repeatability were calculated for each individual. Results: The individual COVs for retinal blood flow for young subjects ranged from 2 to 51.9% (median 28.8%) and for the elderly subjects ranged from 0.6 to 81.2% (median 9.9%). The group mean CORs for retinal blood flow for young subjects were 30.5 μl/min (median 29.5 μl/min, relative to a mean effect 39.8 μl/min) and for elderly subjects were 16.9 μl/min (median 7.2 μl/min, relative to a mean effect 34.7 μl/min). Conclusions: The Doppler SD-OCT in general gave consistent measurements of retinal blood flow in normal subjects, while the data was far more repeatable for the elderly group. The relatively small sample size needs to be considered when interpreting these results.